When More is Less: Understanding Conciseness in Integrated Reporting - Liana Nurul Aini; Ika Permatasari (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The complexity of business activities is pushing for concise, relevant, and comprehensive reporting. Integrated reporting (IR) is a response to the limitations of conventional reporting. In practice, IR is often presented in a lengthy and less integrated, making it less effective as a communication tool with stakeholders. This study examines the role of conciseness in IR and its application in two countries: South Africa and Indonesia. This study used a descriptive qualitative approach with conceptual analysis supported by a comparison of IR from two companies in the banking sector. Data were collected through document analysis of the companies’ 2024 integrated reports. The analysis was based on several indicators, such as the length of the report, the application of the six capitals framework, content elements, guiding principles, and the format of information presentation. The results showed that the level of conciseness is influenced by the interconnection of information, report structure, and the use of visualizations. Reports that are structured in an integrated way and supported by visualizations tend to be more concise, structured, and easy to understand, whereas reports dominated by narrative tend to be longer and less focused. The findings showed that the higher the level of IR adoption maturity, the more concise, structured, and visually-based the resulting reports are, while lower levels of adoption maturity tend to produce longer and less integrated reports.